Myiasis Diagnosis and Treatment in Goat - Niswah Nurul Fahma; Suhiryanto Suhiryanto; Indarjulianto Soedarmanto; Yanuartono Yanuartono; Alfarisa Nururrozi; Hary Purnamaningsih; Slamet Raharjo (Universitas Airlangga, 2020)
Background: Myiasis is a disease caused by an infestation of fly larvae (Chrysomya bezziana) in living tissue. Myiasis cases are common in Indonesia because of the tropical climate. Purpose: This case report is intended to provide information on handling myiasis in goats. Case Analysis: A 2-year-old female goat weighing 30 kg was reported by the farmer because there was a wound in the leg. The goat was examined physically and hematologically. On physical examination, there was a limp on the left front leg caused by an injury with the larvae. Haematological examination results showed leukocytosis with leukocyte count of 13.26 x 103 cells/μL, monocytosis with monocyte counts of 0.63 x 103 cells/μL and anemia with erythrocyte counts of 2.93 x 106 cells/μL. The goat was diagnosed with myiasis and treated by eliminating fly larvae, irrigating the injured part by procaine penicillin and dihydrostreptomycin, spraying the wound using 1% dichlofenthion and intramuscular injection of 20 mg/kg body weight long-acting oxytetracycline and 1 mg/kg body weight diphenhydramine HCl. Conclusion: Three days after treatment, the wound condition has improved.